Economic Philosophy as the Existence of the 5.0 Era Development in Sharia and Conventional Banking - Martania, Mira; Rodiah Nur, Efa (KnE Social Sciences, 2024)
With digital transformation and progress in technology, the 5.0 era has a huge impact on the industry of Islamic and conventional banking. Understanding the existence of Islamic and conventional banking in the 5.0 era relies heavily on economic philosophy. This study aims to understand the role of economic philosophy in maintaining and developing Islamic and conventional banking in the 5.0 era. This study used a descriptive analysis approach, and the data were collected from literature and other relevant sources. Conventional banking, on the other hand, relies on the philosophy of economy neoclassical, which focuses on the development products and services. Islamic and conventional banking are influenced by progress technology and digital transformation in the 5.0 era. Application mobile banking, digital payments, data analytics, artificial intelligence, and blockchain technology are several examples of very important technology or facing challenges and exploiting opportunities in this era. However, in the era of 5.0, economic philosophy is also challenging to apply in Islamic and conventional banking. Conventional banking can notice the difference between the social and financial aspects, but Sharia banking must consider current principles to integrate technology. Sharia and conventional banking need to keep going and develop relevant digital products and services, strengthen regulation and supervision, and guarantee security and privacy of customer’s information. Research results show that good Sharia banking as well conventional are based on economic philosophy. Islamic banking relies on philosophy of Islamic economics, which focuses on principles like prohibition of usury, justice, and sustainable environment. Keywords: philosophy, economics, Sharia, conventional